Estrogen Protects Articular Cartilage by Downregulating ASIC1a in Rheumatoid Arthritis - Hang X; Zhang Z; Niu R; Wang C; Yao J; Xu Y; Tao J; Li L; Chen F (Dove Medical Press, 2021)
Xiaoyu Hang,1,2 Zhenyu Zhang,1,2 Ruowen Niu,1,2 Chen Wang,1,2 Jing Yao,1,2 Yayun Xu,1,2 Jingjing Tao,1,2 Lanlan Li,1,2 Feihu Chen1,2 1Anhui Key Laboratory of Bioactivity of Natural Products, School of Pharmacy, Anhui Medical University, Hefei, 230032, People’s Republic of China; 2The Key Laboratory of Anti-Inflammatory and Immune Medicine, Ministry of Education, Anhui Medical University, Hefei, 230032, People’s Republic of ChinaCorrespondence: Feihu ChenSchool of Pharmacy, Anhui Medical University, No. 81 Meishan Road, Hefei, 230032, Anhui Province, People’s Republic of ChinaTel/Fax +86 551651611166Email chenfeihu@ahmu.edu.cnPurpose: The severity of rheumatoid arthritis (RA) in women is generally lower than that in men. RA is mediated, at least in part, by the protective effects of estradiol. However, the mechanisms underlying the protective effect of estradiol on RA are still unclear. Recent studies have demonstrated that activation of acid-sensing ion channel 1a (ASIC1a) by tissue acidosis plays an important role in the injury of cartilage in RA. Here, we assessed the effects of estradiol on acid-mediated cartilage injury both in vitro and in vivo and explored the involvement of ASIC1a in RA and its underlying mechanism.Methods: Cultured primary articular chondrocytes were subjected to acidosis-mediated injury in vitro. Beclin1, LC3, p62, GPER1, and ASIC1a expression was detected through Western blotting, quantitative real-time PCR, and immunofluorescence analysis. Adjuvant arthritis (AA) was induced in rats through intradermal immunization by injecting 0.25 mL heat-killed mycobacteria (10 mg/mL) suspended in complete Freund’s adjuvant into the left hind metatarsal footpad. The levels of estrogen and related inflammatory factors in the serum were measured using enzyme-linked immunosorbent assay. The expression of ASIC1a and autophagy-related proteins was detected through immunohistochemical analysis and Western blot.Results: Treatment of primary articular chondrocytes with estradiol decreased the expression of ASIC1a and autophagy level. The symptoms of cartilage damage and levels of inflammatory cytokines in the serum were reduced after estradiol treatment in the rats with AA. In addition, estradiol treatment reduced ASIC1a expression via the PI3K-AKT-mTOR pathway, among which G-protein coupled estradiol receptor 1 (GPER1) plays a regulatory role. Finally, the level of autophagy in chondrocytes was decreased by the selective ASIC1a blocker psalmotoxin-1 (PCTX-1).Conclusion: Estradiol can protect the cartilage of rats with AA against acidosis-mediated damage and autophagy by suppressing ASIC1a expression through GPER1.Keywords: rheumatoid arthritis, estradiol, GPER1, ASIC1a, autophagy, PI3K-AKT-mTOR